EXPERIMENTAL DETERMINATION AND ANALYSIS OF THE SOLUBILITY OF CORUNDUM IN 0.1 AND 0.5 M NACL SOLUTIONS BETWEEN 400 AND 600°C FROM 0.5 TO 2.0 KBAR - Walther J.V. (My University, 2001)
Corundum, α-Al2O3, solubility was measured in 0.1 and 0.5 m NaCl solutions from 400 to 600°C between 0.5 and 2.0 kbar. The base-10 logarithm of Al molality at 2 kbar in 0.5 m NaCl increases from -2.45 at 400°C to -1.52 at 600°C. At 1 kbar, the solubility increases from -2.33 at 400°C to -1.03 at 600°C. These molalities are between 1 and 3 orders of magnitude greater than corundum solubility in pure H2O (Walther, 1997). In 0.1 m NaCl, corundum solubility begins to decrease below that in pure water at 400°C as pressures are decreased below ~1.2 kbar. A distribution of species calculation considering the Al species NaAl(OH)40, Al(OH)30 and Al(OH)4- and using association constants reported in the literature demonstrate that Al(OH)4- is a significant species in equilibrium with corundum in pure H2O. The calculations also indicate that another Al aqueous species containing Na or Cl besides NaAl(OH)40 must be present in NaCl solutions to give the observed increase in Al with increasing NaCl concentrations to 0.5 m.